Natural Peccei-Quinn symmetry in the 3-3-1 model with a minimal scalar sector - Montero, J. C. [UNESP]; Sánchez-Vega, B. L. [UNESP] (American Physical Society (APS), 2011)
In the framework of a 3-3-1 model with a minimal scalar sector we make a detailed study concerning the implementation of the Peccei-Quinn symmetry in order to solve the strong CP problem. For the original version of the model, with only two scalar triplets, we show that the entire Lagrangian is invariant under a Peccei-Quinn-like symmetry but no axion is produced since a U(1) subgroup remains unbroken. Although in this case the strong CP problem can still be solved, the solution is largely disfavored since three quark states are left massless to all orders in perturbation theory. The addition of a third scalar triplet removes the massless quark states but the resulting axion is visible. In order to become realistic the model must be extended to account for massive quarks and an invisible axion. We show that the addition of a scalar singlet together with a ZN discrete gauge symmetry can successfully accomplish these tasks and protect the axion field against quantum gravitational effects. To make sure that the protecting discrete gauge symmetry is anomaly-free we use a discrete version of the Green-Schwarz mechanism. © 2011 American Physical Society.